Delegation and Strategic Compensation in Tournaments - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
This paper considers a two-stage game with two owners and two managers. On the first stage, the owners choose a linear combination of profits and sales as incentives for their managers. On the second stage, the two managers compete in a tournament against each other. In a symmetric equilibrium, both owners induce their managers to maximize profits. In asymmetric equilibria, however, one owner puts a positive weight on sales and the other a negative weight.
Keywords: 330